Evaluadores Volúmen 34(1) (RUNA, archivo para las ciencias del hombre, 2013)
Evaluadores ExtranjerosRachel Aisengart Menezes  - UFJR, Rio JaneiroAdela Franzé - UCM, EspañaJosé Reginaldo Gonçalvez - UFRJ, BrasilAna María Rosas Mantecón - UAM Iztap., MéxicoEvaluadores NacionalesMaría Epele - FLACSO / CONICETMariana Giordano - UNNE Carina Kaplan - UBA